Bioactive compounds of deep eutectic solvents extracts of Hypericum perforatum L.: Polyphenolic- organic acid profile by LC-MS/MS and pharmaceutical activity. (October 2022) - Bayram, Sinan; Kutlu, Naciye; Gerçek, Yusuf Can; Çelik, Saffet; Ecem Bayram, Nesrin
Abstract: Deep eutectic solvents (DESs) are known as environmentally-friendly solvents that have emerged as an alternative to conventional organic solvents in recent years. In this study, the effects of ten different DESs on the extraction of bioactive components from the Hypericum perforatum were investigated. Total phenolic content, total flavonoid content, phenolic profile (32 phenolics), organic acid profile (52 organic acids), as well as antioxidant and antimicrobial activities of H. perforatum extracts prepared using DESs and ultrasonic-assisted extraction method were determined. Total phenolic, total flavonoid content, and antioxidant activities of extracts were determined between 3.10 ± 0.86–16.64 ± 2.09 mg GA/g, 0.02 ± 0.00–12.29 ± 0.30 mg QE/g, and 8.40 ± 0.50–44.78 ± 2.66 mg TE/g, respectively. DES2 (choline chloride:ethylene glycol) and DES7 (choline chloride:lactic acid) demonstrated higher extraction success than other DESs for extracting phenolics and organic acids, respectively. DESs prepared using organic acid as hydrogen bond donor were found to have an antibacterial effect against all bacterial samples. However, the inhibitory effect against yeast-like fungi was observed in a narrower spectrum. Moreover, the results from principal component analysis also confirmed that the type of solvent used for extraction has a significant influence on the phenolics, organic acid, and other parameters. As a result, it was seen that DES components directly affect the extraction efficiency of target compounds from H. perforatum . This is a first and original report about use of DESs in extracting different bioactive components from H. perforatum. Graphical abstract: Image 1 Highlights: Hypericum perforatum was extracted using ten different DES. Fifty-two organic acids were investigated by LC-MS/MS in DES extracts. Thirty-two phenolics were scanned by LC-MS/MS in DES extracts. DESs prepared using organic acids showed antibacterial activity against bacteria. PCA confirmed that the solvent type has a significant influence on all parameters.